2006
DOI: 10.1017/s0022215106005032
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of presentation and diagnosis of patients with Wegener's granulomatosis: ENT aspects

Abstract: Design: a cross-sectional study.Participants: One hundred and ninety-nine patients with Wegener's granulomatosis belonging to a patient self-help group.Main outcome measures: Mode of initial presentation; diagnosis timescales and delay; rhinologic involvement; and treatment.Results: Sixty-three per cent of patients initially presented with ENT-related symptoms. Ninety-two per cent faced a delay in their diagnosis of more than one month, a pattern which has not improved over the last few decades and which compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
70
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 5 publications
3
70
2
Order By: Relevance
“…In contrast to our case, a recent study found that patients older than 60 years when diagnosed with GPA initially presented with renal, pulmonary and other manifestations more so than younger patients [7]. This study also found that the nose and paranasal sinuses in particular, were the sites of presenting symptoms in 50 per cent of patients diagnosed before the age of 60 years, compared with only 27 per cent of those diagnosed when older than 60 years.…”
Section: Discussioncontrasting
confidence: 97%
“…In contrast to our case, a recent study found that patients older than 60 years when diagnosed with GPA initially presented with renal, pulmonary and other manifestations more so than younger patients [7]. This study also found that the nose and paranasal sinuses in particular, were the sites of presenting symptoms in 50 per cent of patients diagnosed before the age of 60 years, compared with only 27 per cent of those diagnosed when older than 60 years.…”
Section: Discussioncontrasting
confidence: 97%
“…Therefore ENT doctors should be more careful in diagnosis. [1] As in our case, when the patient consults with limited symptoms of WG and rare organ involvement (like the parotid gland), it is important to have a high index of suspicion. [16] For this reason, ENT doctors should not overlook WG in the differential diagnosis of patients with chronic inflammation and head and neck region involvement that is non responsive to medical therapy.…”
Section: Discussionmentioning
confidence: 74%
“…Sirouji et al [1] showed that time from consultation with presenting symptoms to the definite diagnosis was >1 month in 92% of the patients. Early diagnosis and appropriate treatment can prevent disease progression, as the disease can convert into a systemic, irreversible form with lung and kidney involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Recognising patients with secondary chronic rhinosinusitis, who have normal sinuses despite being convinced otherwise, is sometimes as difficult as managing those patients mentioned above. Valerie Lund's experience of vasculitis in the nose and sinuses is unparalleled; the manifestations of Wegener's in nearly 200 patients are described in a paper by Srouji et al 11 A top tip, straight from Professor Lund, is to ask all patients if they 'feel unwell' -a positive response should prompt consideration of systemic disease.…”
mentioning
confidence: 99%